Anytime Computation of Cautious Consequences in Answer Set Programming. Issue 4 (21st July 2014) - ALVIANO, MARIO; DODARO, CARMINE; RICCA, FRANCESCO; Leuschel, Michael; Schrijvers, Tom
Abstract Query answering in Answer Set Programming (ASP) is usually solved by computing (a subset of) the cautious consequences of a logic program. This task is computationally very hard, and there are programs for which computing cautious consequences is not viable in reasonable time. However, current ASP solvers produce the (whole) set of cautious consequences only at the end of their computation. This paper reports on strategies for computing cautious consequences, also introducing anytime algorithms able to produce sound answers during the computation.